Numerical simulation analysis of pile-soil interaction under earthquake action - Yifei Wang; Zhanfang Huang; Ruixue Hu; Lichao Bai; Junjie Zheng; Yi Chen; Xiaohong Bai (PLoS ONE, 2025)
Pile foundation is a commonly recognized form of foundation, and earthquakes are a common seismic damage phenomenon. Accidents resulting from reduction in pile bearing capacity due to earthquakes pose a great threat to people’s lives and safety. This article investigates the interaction between soil and piles under earthquake action. Utilizing the MIDAS GTS NX finite element software, the vertical bearing characteristics of piles under earthquake action are studied. Obtained acceleration of piles, pile settlement, pile axial force, pile top horizontal displacement, soil pore water pressure, and pore pressure ratio under different earthquake magnitudes. The research results indicate that as the depth increases, the acceleration at the pile top is significantly greater than that at the pile bottom, with an average increase of 20% in acceleration at three different earthquake magnitudes; Both the beginning of the pore pressure ratio growth and the ultimate reaching of its stable pore pressure ratio coincide with a rise in earthquake magnitude. Additionally, the axial force of the pile body also increases with the magnitude of the earthquake, and the maximum axial force of the pile body can increase by 40% at the same time. Simultaneously, the magnitude of the earthquake influences both the displacement of the pile body and the settling of the pile top. This article can provide reference for pile foundation design and engineering construction in liquefaction sites.